An Investigation Of The Genetic Polymorphisms Of N-Acetyltransferase 2 In Healthy Malays, Chinese And Indians In Malaysia And In Tuberculosis Patients On Isoniazid - Yusuf, Wan Nazirah Wan (2006)
N-acetyltransferases are enzymes found in the liver, the small intestines, urinary bladder, lungs and skin. They mediate Phase II metabolism of xenobiotics containing an aromatic amine or a hydrazine group. They are genetically polymorphic with several important SNP's. Their substrates include INH, pro-carcinogens and carcinogens. They therefore have importance in the pathogenesis of some cancers and in the pharmacotherapy of some diseases, notably tuberculosis. The objective of our study is to investigate the types and frequencies of NAT2 polymorphisms in the three major ethnic groups in Malaysia and among TB patients to forecast their influence on the rate of metabolism of INH. Malay, Chinese and Indian healthy volunteers were recruited from blood donation drives and their blood was taken for NAT2 genotyping. Newly diagnosed TB patients were also recruited. Blood for genotyping and phenotyping were collected at 4 hours after INH ingestion in patients who were treated with INH. Genotyping was done using nested allele specific multiplex peR methods and phenotyping by measuring plasma INH and Act-INH on the HPLC. Among healthy volunteers, the frequencies for NAT2*4, NAT2*5, NAT2*6, NAT2*7 and NAT2*12 in the 212 Malays, 172 Chinese and 175 Indians were 43.4%, 10.6%,25.5%,16.3% and 4.3% respectively among Malays; 64.0%, 3.2%,16.3%,12.2% and 0.3% among Chinese; and 22.6%,30.6%,30.9%, 6.9% and 3.4% among Indians. The types and frequencies for NAT2 alleles in TB patients were NAT2*4, NAT2*5, NAT2*6, NAT2*7 and NAT2*12 at 47.4%, 14.0%,21.2%, 12.9% and 2.3% respectively. The most common genotypes were NAT2*4/*4, NAT2*41*7, NAT2*4/*5 and NAT2*6/*6 with the frequencies of 25%, 18.9%, 15.2% and 15.2% respectively. There was no significant difference in allele frequencies of TB patients and healthy volunteers. For the 62 patients phenotyped, INH concentrations ranged from 0.31 to 4.17 j.Jg/ml and for Act-INH concentration from 0.01 to 2.48 j.Jg/ml. There was a trend for the metabolic ratios to increase with genotypes that predicted poorer activity. Correlation of genotype to MR was however imperfect.